Evaluation of students’ dietary behaviours depending on gender - Daniuseviciute-Brazaite, Laura; Abromaitiene, Laima (Progress in Nutrition, 2018)
It is believed that university students commit many nutritional errors due to changes in lifestyle such as moving away from the family home, irregular meals, long hours spent studying, and frequently taking part-time jobs. Thus, we aimed to a) describe the baseline dietary intake of university students, b) identify differences in healthy eating between genders, and c) explore the relationship between lipoproteins and anthropometric data. In total, 500 students, 339 females and 161 males from Lithuanian universities and colleges participated in the study. The Food Frequency Questionnaire was used to evaluate dietary habits. The body composition values and blood analysis were estimated. Most participants (74.3%) reported regularly eating breakfast on weekdays, but of those, less than half ate breakfast 1-2 days a week. Females were more likely to consume cooked vegetables, salad/raw vegetables, fresh fruits, and curd-/cream cheese/yoghurt (p<0.001). By comparison, consumption of red meat, poultry, sausages, fish, and hard/soft cheeses (p<0.001) was common among males. In addition, males ate fast food (p<0.001) more often than females. Females consumed chocolate more often than males did (p<0.001). In males, total cholesterol, triglycerides, and low density lipoprotein (LDL) cholesterol were correlated with body weight and body mass index (BMI) (p <0.01). In females, high density lipoprotein (HDL) cholesterol was negatively correlated with body weight and BMI (p<0.01). The main barriers to healthy eating were identified as skipping breakfast and deficiencies in the consumption of specific food groups such as fruits and vegetables as recommended by the World Health Organisation (WHO). With respect to gender, differences in healthy eating were found in the consumption of meat and regular meals. The degree of obesity, triglycerides, and LDL cholesterol were higher in males, suggesting possible association with chronic disease incidence such as hyperlipidaemia and hypertension.